Enhancing agency in green path development : Lessons from the wind energy sector for the emerging battery industry in the Nordic region - Okonkwo, Ejike (Society for Scientific Aptitude, 2025)
This paper reviews the literature on wind energy to ascertain the factors that shape agency in the sector's development trajectory and then extract valuable lessons that regional actors can leverage in the emerging Nordic battery industry. The research process is anchored on the READ approach, i.e., readying, extraction, analyzing, and distilling. The results show that agency is shaped by socio-cognitive, economic, geographical, and cultural factors. Actors' actions must, therefore, proactively align the battery development strategies to the cultural context, taking cognizance of the norms, values, stakeholder involvement, and participation. By taking the lessons from the wind energy sector, this paper provides a scientific insight that regional actors can leverage to navigate similar experiences and challenges in the battery development process in the Nordic region easily. This paper advances cross-sector knowledge in the green path development literature
Keywords: Agency; cross-sector knowledge; green path development; Nordic battery industry; Nordic region; wind energy technologies; fi=Aluetiede|en=Regional Studies|